Comparison of Color Change to pH Range and Acid-Base Titration Indicator Precision Test of Multiple Ethanol Extracts - Tuslinah, Lilis; Yuliana, Anna; Arisnawati, Dian; Rizkuloh, Lina Rahmawati (Trends in Sciences, 2021)
Natural indicators using anthocyanin compounds can be an alternative to synthetic indicators on acid-base titration because anthocyanin is an organic compound that is unstable with changes in pH. The extraction was carried out with ethanol because the compounds of anthocyanin were polar. This study was to ensure an ethanol extract of some plants could be used as an acid-base indicator that had a pH range of color change and the value of the equality parameter was not significantly different from the phenolphthalein indicator. The research method is to collect research journals on making natural indicators from ethanol extracts of various plants compared to phenolphthalein indicators so that secondary data from these journals can be processed statistically. Research results and conclusions: Based on the results of statistical data processing using the t-test there was no difference in the average pH of the phenolphthalein indicator with the average pH of ethanol extracts of adam air leaves (Rheo discolor), white frangipani flowers and Clitoria teratea L., with a significance value > 0.05 and the equality test (precision) had the requirements of good equality. HIGHLIGHTS Natural indicators are needed as a substitute for synthetic indicators in determining acid-base titrations; one of them is anthocyanin dye Research journals on making natural indicators from ethanol extracts of various plants compared to phenolphthalein indicators so that secondary data from these journals can be processed statistically There was no significant difference between the average pH of the phenolphthalein indicator and the average pH of the ethanol extract of Adam's Eve Leaves, ethanol extracts of white Cambodia flowers and ethanol extracts of Telang flowers in producing color changes GRAPHICAL ABSTRACT